Investigation of Kerr effect in a blue phase liquid crystal using wedge-cell technique - Orzechowski, Kamil; Sierakowski, Marek Wojciech; Sala-Tefelska, Marzena; Woliński, Tomasz Ryszard; Strzeżysz, Olga; Kula, Przemysław (Photonics Letters of Poland, 2017)
In this work an alternative method for refractive index measurement of blue phase liquid crystal in the Kerr effect has been described. The proposed wedge method uses simple goniometric setup, allowing for direct index measurements for any wavelengths and index values. This is significant advantage comparing to other methods, usually having limitations of the measurement range as well as necessity complicated calculation to obtain refractive indices values. The results are reliable and agree well with the subject literature. Full Text: PDF References W. Cao et al., "Lasing in a three-dimensional photonic crystal of the liquid crystal blue phase II", Nat. Mater. 1, 111-113 (2002). CrossRef S. Meiboom, M. Sammon, W.F. Brinkman, "Lattice of disclinations: The structure of the blue phases of cholesteric liquid crystals", Phys. Rev. A. 27, 438 (1983). CrossRef S. Tanaka et al., "Double-twist cylinders in liquid crystalline cholesteric blue phases observed by transmission electron microscopy", Sci. Rep. 5, 16180 (2015). CrossRef Y. Li and S.-T. Wu, "Polarization independent adaptive microlens with a blue-phase liquid crystal", Opt. Express 19(9), 8045-8050 (2011). CrossRef N. Rong et al., "Polymer-Stabilized Blue-Phase Liquid Crystal Fresnel Lens Cured With Patterned Light Using a Spatial Light Modulator", J. of Disp. Technol. 12(10), 1008-1012 (2016). CrossRef J.-D. Lin et al., "Spatially tunable photonic bandgap of wide spectral range and lasing emission based on a blue phase wedge cell", Opt. Express 22(24), 29479-29492 (2014). CrossRef P. Joshi et al., "Tunable light beam steering device using polymer stabilized blue phase liquid crystals", Photon. Lett. Poland 9(1), 11-13 (2017). CrossRef Ch.-W. Chen et al., "Temperature dependence of refractive index in blue phase liquid crystals", Opt. Mater. Express 3(5), 527-532 (2013). CrossRef Y.-H. Lin et al., "Measuring electric-field-induced birefringence in polymer stabilized blue-phase liquid crystals based on phase shift measurements", J. Appl. Phys. 109, 104503 (2011). CrossRef J. Yan et al., "Direct measurement of electric-field-induced birefringence in a polymer-stabilized blue-phase liquid crystal composite", Opt. Express 18(11), 11450-11455 (2010). CrossRef K.A. Rutkowska, K. Orzechowski, M. Sierakowski, "Wedge-cell technique as a simple and effective method for chromatic dispersion determination of liquid crystals", Photon. Lett. Poland 8(2), 51-53 (2016). CrossRef O. Chojnowska et al., "Electro-optical properties of photochemically stable polymer-stabilized blue-phase material", J. Appl. Phys. 116, 213505 (2014). CrossRef J. Yan et al., "Extended Kerr effect of polymer-stabilized blue-phase liquid crystals", Appl. Phys. Lett. 96, 071105 (2010). CrossRef M. Chen et al., "Electrically assisting crystal growth of blue phase liquid crystals", Opt. Mater. Express 4(5), 953-959 (2014). CrossRef J. Kerr, Philos. Mag. 50, 337 (1875).